Clinical profile of dengue fever patients in tertiary care hospital of North India - Dr. Sheo Pratap Singh; Dr. Madhu Nayak; Dr. Madhu Singh; Dr. Ram Kshitij Sharma; Dr. Sheshadri Singh (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: In India, Dengue epidemics are becoming more frequent. The majority of dengue virus infection are self limiting, but complications may cause substantial morbidity and mortality. Methods: In this retrospective study, medical records were reviewed and analyzed. Patients were classified into dengue with and without warning sign and severe dengue (DHF/DSS). Objectives: To assess clinical profile of dengue infection in children less than 18 years of age and to evaluate outcome of dengue fever admitted from June to December 2018, in Department of Pediatrics, Sarojini Naidu Medical College, Agra. Results: A total of 50 dengue positive patients were classified into dengue with or without warning signs 42(84%) and 8 (16%) severe dengue cases. The most commonly involved children were male between 5-10 yr (36%) of age group followed by 1-5 yr (34%). Most common clinical manifestation was fever observed in 96% cases followed by rash (66%), pain abdomen (52%) and vomiting in 26% cases.46% cases of dengue had warning signs. Most common clinical and radiological findings were ascites seen in 24% cases followed by pleural effusion. Elevation of Aspartate Transaminase (SGOT) in 82% and thrombocytopenia was seen in 60% cases. Conclusion: High grade fever, vomiting, abdominal pain and skin rash with normal or low platelet count were varying clinical presentation. Early clinical suspicion and diagnosis with prompt management accompanied by preventive measures can prevent morbidity and the mortality associated with dengue.